The Traffic Jam Phenomenon at Traditional Village: A Case of User Perception in Batam, Indonesia - Tria Resinta; Andri Irfan Rifa’i (Fakultas Teknik Sipil dan Perencanaan, 2023)
The development of transportation is increasing day by day. Increased transportation can cause a problem, especially land transportation; the problem is traffic congestion. The road in Simpang Mangsang, Tanjung Piayu, Batam City, is clear proof of the traffic congestion caused by the problem of lousy intersection direction. This is done research related to the problems that occur. This study was conducted by distributing a 100-form questionnaire that will be responded to by motorists passing through the road. The purpose of this study is to find out the condition of the road when there is a traffic jam. The results of this study obtained an excellent average score on the importance assessment, which was 3.90. This value is the primary interest that results from the driver's response. Furthermore, it needs even better improvement and obtained the average score of the satisfaction assessment when there is a traffic jam, which is 2.18. This is a slightly weak satisfaction score due to the problem's congestion.